SECURING HAZARDOUS IoT SENSOR DEVICE WITH PATCH MANAGEMENT USING TWO PHASE AUTHENTICATION - Suresh, A.; Naidu, G.T. (International Journal of Psychosocial Rehabilitation, 2020)
Security in IoT security is the novelty zone concerned about defending linkeddigital media and systems in Internet of things (IoT). IoT comprised with adding web ease of use to an agreement of consistentbuildin gadgets, with advanced mechanical machines, items, creationswith add on’s digital content. Every "thing" as digital media is given an identifier and the ability to naturally transform information over information system. Permitting digital gadgets to edge with the web frees them up to various genuine weaknesses on the off probability that they are not properly secured. Secure IoT has been converted into the examination subsequent to various majorevents where a characteristic IoT gadget was utilized to invade and assault the bigger system. Actualizing hazardous safety efforts is basic to assurance the wellbeing of IoT gadgets associated with them. This work addresses IoT patch management is implemented in hazardous IoT devices that enhances automatic security as it seems to be crucial. The vulnerabilities in IoT rise when the IoT devices are updated. Using patch management the IoT devices uses two phase authentication for ensuring the devices are secured and free from vulnerabilities. The security is evaluated based on the device security implication and the device performance is degraded when there is a security flaw.